PENGEMBANGAN E-LKPD GAMBUT RIAU BERBASIS PENDEKATAN SOCIO-SCIENTIFIC ISSUES (SSI) PADA MATERI EKOSISTEM KELAS X SMA - Wulandari, Meilani; Mariani Natalina L.; Fitra Suzanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of biology teaching materials, especially E-LKPD on ecosystem topics, has not fully met the demands of Merdeka Curriculum which emphasizes contextual, critical, and locally relevant learning. This research and development study aims to produce a high-quality Electronic Student Worksheet (E-LKPD) on Riau Peatland ecosystems integrated with the Socio-Scientific Issues (SSI) approach for Grade X SMA students. The development used the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), carried out through the Analysis, Design, and Development stages. Validation was conducted by three validators (one lecturer and two biology teachers) covering media validity (graphic components, presentation, language, and practicality) and material validity (content feasibility, learning effectiveness, and SSI integration). Limited trials were conducted in two phases: Phase I involved 10 university students from Biology Education at Universitas Riau, and Phase II involved 30 Grade X students at SMAN 8 Pekanbaru. Results showed an overall validation mean score of 3.62 (very valid). Trial Phase I yielded a mean of 3.71 (very good) and Trial Phase II yielded a mean of 3.58 (very good), resulting in a final product quality score of 3.64 (very good). These findings indicate that the developed E-LKPD is valid and practical for facilitating higher-order thinking, ecological literacy, and evidence-based decision-making skills through the integration of authentic Riau peatland issues.